А нас и здесь неплохо кормят!: повесть-сказка: [12+] / А. Курляндский ; [худ. О. Ю. Горбушин, В. А. Караваев] - Курляндский Александр Ефимович (Наши любимые мультфильмы, 2009)
Экземпляры: ф.11 (20131217) / Инвентарный номер: 45431 / Цена: 83.00 / Авт.знак: К 93 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6